Bridging the Standard Operating Procedures between Creative Departments Personnel in Shopping Malls - Chong, Yee Yang; Qistina Donna Lee, Abdullah (2015)
The aim of this paper is to analyze and introduce a new set of Standard Operating Procedure (SOP) in the creative department in selected Shopping Malls in Kuching, and Kota Samarahan, Sarawak. SOP is a set of written guideline or instruction that can be followed by personnel in a department. SOP acts as a detailed written document that guides employees and ensure the working flow is at its optimum usage. Apart from that, SOP is also executed as a bridge between the employees and their daily job descriptions. Through preliminary research, two main problems have been identified such as creative departments work without implementation of SOP, and the departments in their organizations have inefficient rules and guidelines in delivering their daily routines. By recognizing these challenges, the hypothesis of this research is through the proposed new set of SOP that will give advantage for management team to manage and monitor the creative department more efficiently. Consequently, in this first phase of this theoretical study, a few SOP models and frameworks will be analyzed and explored in terms of the relevancy and significant elements before being adapted as a research outcome.